Late Miocene Tapiridae from Vallès-Penedès Basin (NE Iberian Peninsula): taxonomic and paleoenvironmental implications - Luca Pandolfi; Sara G. Arranz; Sergio Almécija; Jordi Galindo; Àngel H. Luján; Marta Pina; Alessandro Urciuoli; Isaac Casanovas-Vilar; David M. Alba (Swiss Journal of Palaeontology)
Abstract European Miocene tapirs (Perissodactyla, Tapiridae) are mainly documented by isolated and fragmentary remains, and little is known about the morphological variability of the various recognized species, in particular concerning the deciduous dentition. Here, we describe new material from three Vallesian (Late Miocene) sites of the Vallès-Penedès Basin (NE Iberian Peninsula): Creu de Conill 20 (CCN20; earliest MN9, 11.2 Ma), Can Llobateres 1 (CLL1; earliest MN10, 9.8 Ma), and Can Gambús-Illeta 5 (CGS-I5; MN10, 9.7–9.1 Ma). The described material, including previously reported specimens from CLL1, consists of a juvenile cranium as well as deciduous and permanent teeth, which are compared with those of Late Miocene tapirid species from Europe (Tapirus priscus, Tapirus antiquus, Tapiriscus pannonicus, Tapiriscus balkanicus, and Tapirus arvernensis), supporting an attribution to T. priscus. The Vallès-Penedès specimens provide further insight into the morphological variability of T. priscus, particularly regarding its deciduous dentition, as well as its distinction from T. arvernensis. Tapirus priscus occurred in Western Europe during the early and late Vallesian (MN9–MN10) and became extinct in Central Europe during the early Turolian (MN11), leaving a gap in the fossil record of Tapirus until the arrival of T. arvernensis at the MN13–MN14 transition. From a paleoecological perspective, the presence of Tapirus agrees with paleoenvironmental reconstructions of CLL1 as a humid and densely forested wetland/riparian forest with more open areas nearby, while the CGS-I5 material attests to the persistence of such kind of environments in the Vallès-Penedès Basin sometime into the late Vallesian. In contrast, the occurrence of Tapirus is at odds with previous paleoenvironmental inferences for CCN20, which indicated a more open and arid environment, suggesting that the earliest Vallesian in this basin was characterized by more humid and forested conditions than previously assumed (in further agreement with the roughly coeval site of Castell de Barberà).